2020
DOI: 10.1021/acsenergylett.0c01063
|View full text |Cite
|
Sign up to set email alerts
|

Hot Hole Transfer Dynamics from CsPbBr3 Perovskite Nanocrystals

Abstract: Transfer of the hot charge carriers prior to their cooling to the band-edge states can enhance the efficiency of a semiconductor-based solar cell much beyond its Shockley–Queisser (SQ) limiting value. Herein, we explore transfer of hot holes from the APbBr3 nanocrystals (NCs) employing a carefully chosen molecular system, 4-mercaptophenol. Ultrafast pump–probe and fluorescence measurements indeed confirm this transfer process, whose efficiency depends on the energy content of the hole, and a maximum efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 57 publications
(84 reference statements)
4
73
1
Order By: Relevance
“…Extraction of hot charge carriers is a challenging task due to their rapid relaxation to the band-edge states. Only a few reports of HC extraction from perovskites are so far available. ,,,− In an early work, transfer of hot electron and hot hole from CsPbBr 3 NCs to BQ and PTZ was established by monitoring the photoinduced change in conductivity in time-resolved THz transmission . Li et al showed transfer of hot electrons from MAPbBr 3 to 4,7-diphenyl-1,10-phenanthroline (Bphen) from the sharp drop in bleach amplitude at early time in the presence of the latter.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Extraction of hot charge carriers is a challenging task due to their rapid relaxation to the band-edge states. Only a few reports of HC extraction from perovskites are so far available. ,,,− In an early work, transfer of hot electron and hot hole from CsPbBr 3 NCs to BQ and PTZ was established by monitoring the photoinduced change in conductivity in time-resolved THz transmission . Li et al showed transfer of hot electrons from MAPbBr 3 to 4,7-diphenyl-1,10-phenanthroline (Bphen) from the sharp drop in bleach amplitude at early time in the presence of the latter.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Further details about the setup can be found elsewhere. [51] Fourier transformed infrared spectroscopy (FTIR): FTIR measurements were performed using Bruker Tensor II spectrometer. Single drop of colloidal solution of as-synthesized and treated CsPbBr 3 NCs was used from the stock solution (in hexane).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Solar cells, fuel cells, and rechargeable batteries have become fundamental tools for energy storage, with lithium-ion batteries (LIBs) having gained great popularity because of their low ecological footprint, high energy density, and good cycle life. Nevertheless, LIBs have major drawbacks, including their carbon anodes having a theoretical capacity of only 372 mAh g –1 , which must be addressed. At present, lithium batteries often contain poisonous metals, which bring into consideration huge energy utilization and climate contamination, particularly for bulk energy storage applications. Although industrially used LIBs have electrodes of inorganic origin, these materials are hazardous and scarce, leading to sustainability issues . The advancement of organic cathode materials for battery-powered applications has been moderate in comparison with that of inorganic cathode materials. Organic materials have unique advantages when used as cathode materials, including facile molecular engineering, , low cost, high abundance, environmental friendliness, and high theoretical capacities .…”
Section: Introductionmentioning
confidence: 99%
“…5−7 Although industrially used LIBs have electrodes of inorganic origin, these materials are hazardous and scarce, leading to sustainability issues. 8 The advancement of organic cathode materials for battery-powered applications has been moderate in comparison with that of inorganic cathode materials. 9−11 Organic materials have unique advantages when used as cathode materials, including facile molecular engineering, 2,12 low cost, high abundance, environmental friendliness, and high theoretical capacities.…”
Section: ■ Introductionmentioning
confidence: 99%